Gerakan Julid Fisabilillah - Santi, Selvia (Indonesia Center for Middle East Studies, 2024)
Israel's military aggression against the Gaza Strip, which began on October 7, 2023, has become one of the most important issues in the world thanks to the role of social media, which massively disseminates events on the ground and counters the mainstream media narrative, which tends to be pro-Israel. Social media has been actively used by internet citizens around the world to defend Palestine. In Indonesia, a movement emerged on social media called